PENGARUH CONTENT MARKETING DAN INFLUENCER TERHADAP MINAT BELI KONSUMEN PT. MAKMUR DEKORINDO LESTARI MEDAN - Afrina, Afrina; Margery, Errie; Seri, Seri (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research was conducted on consumers at PT. Makmur Dekorindo Lestari Medan. The purpose of this research is to determine and analyze the influence of Content Marketing and Influencers on Consumer Purchase Interest. The population and sample in this study amounted to 45 people. The sampling technique used was saturated. The data collection technique is by distributing questionnaires and interviews. Data analysis uses multiple linear regression analysis. The conclusion in the research is that simultaneously Content Marketing and Influencers have a positive and significant effect on PT Consumer Buying Interest. Makmur Dekorindo Lestari Medan. Partially, Content Marketing influences PT Consumer Buying Interest. Makmur Dekorindo Lestari Medan. Partially, Influencers have no influence on PT Consumer Buying Interest. Makmur Dekorindo Lestari Medan. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value of 0.188 or 18.8% and the remaining 81.2% is influenced by other factors outside the research model such as sales promotion, personal selling, service quality, advertise, influencer credibility, WOM, live streaming, etc.